How do teachers respond to prescriptive curriculum changes? a study in teacher discourse about educational reform. - Pugh, Thomas (My University, 2012)
How do teachers respond to being told by the state what to teach? Whilst some suggest prescription can be instrumental in rapid system improvements, others believe that it has a deleterious effect on the profession. In this study, I firstly look at whether South Africa can be classified as a system increasing its levels of prescription and secondly consider how such an approach may affect teachers. Detailed investigation of policy documents finds that South African primary mathematics is an example of ‘unprescribed prescription’, typified by documents with hugely detailed teaching and learning practices but which are never made sufficiently mandatory. Studies of teachers’ responses to prescriptive educational reform are hindered by stereotypes, often based around teachers’ unwillingness to change. In-depth interviews allow the study to explore the positive and negative effects which teachers’ professional identities have upon decisions regarding policy reform. Equally, far from being passive in their reception of change, teachers displayed highly-ordered and well-reasoned viewpoints on how educational change should be successful. This allowed me to place teachers into four discrete categories according to their response to prescription and the implications of these categories for policy makers are put forward.
Keywords: Elementary teachers; Comprehensive school reform; Prescription; Instruction; School reform; Educational change